2014
DOI: 10.14814/phy2.12076
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of the promoter of the catalytic subunit of protein phosphatase 2A in response to hyperglycemia

Abstract: In order to identify epigenetic mechanisms through which hyperglycemia can affect gene expression durably in β cells, we screened DNA methylation changes induced by high glucose concentrations (25 mmol/L) in the BTC3 murine cell line, using an epigenome‐wide approach. Exposure of BTC3 cells to high glucose modified the expression of 1612 transcripts while inducing significant methylation changes in 173 regions. Among these 173 glucose‐sensitive differentially methylated regions (DMRs), 14 were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Recently, CISH has emerged as an important modulator of β-cell insulin desensitization following prolonged glucose exposure. It has been reported that the expression and DNA methylation of CISH alter in response to hyperglycemia (22). Furthermore, the expression of CISH proteins is upregulated in islet cells from patients with T1D compared with healthy individuals (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CISH has emerged as an important modulator of β-cell insulin desensitization following prolonged glucose exposure. It has been reported that the expression and DNA methylation of CISH alter in response to hyperglycemia (22). Furthermore, the expression of CISH proteins is upregulated in islet cells from patients with T1D compared with healthy individuals (23).…”
Section: Discussionmentioning
confidence: 99%